Challenging Efforts to Find African Swine Fever Vaccine - Simson Tarigan (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
African swine fever (ASF) has been endemic in Indonesia and neighbouring countries. So far, the only reliable measure to eradicate the disease has been the application of strict biosecurity and culling of all infected pigs. This method is not feasible in Indonesia because most pig farms are small with a deficient level of biosecurity. Vaccination would be the most practical control measure, but no vaccine has been available for ASF. The difficulties encountered in developing the ASF vaccine lie in the fact that the ASF virus is very complex, with a sophisticated ability to paralyze the host immune system. ASF virus infects monocytes and macrophages, causing the cells to lose their functions to mount immune responses, further complicating vaccine development. Killed vaccines, even those containing complete structural and non-structural proteins of the virus and fortified with potent adjuvants for both humoral and cellular immune responses, were practically incapable of inducing protective immunity. Subunit vaccines containing recombinant viral proteins have also been developed, but none have provided satisfactory protection even though the vaccine indicates neutralizing antibodies. Live vaccines prepared from naturally low virulent viral strains or by repeated attenuation in cell cultures provided more satisfactory protective immunities than the inactive or subunit vaccines. However, their use in the field had caused severe side effects because the mutant still had residual virulence. Live vaccines prepared by deleting genes that play a role in virulence have been the most promising approach. Several mutants that were no longer virulent but capable of inducing protective immunity have been identified; however, lengthy safety testing is still needed before this vaccine is commercially available.